IVUS Assessment of the Crossing Pathway of an Intraluminal Reentry Device Used in the Primary Treatment of Infrainguinal Chronic Total Occlusions. (February 2020) - Tomoi, Yusuke; Takahara, Mitsuyoshi; Fujihara, Masahiko; Fukunaga, Masashi; Iwasaki, Yusuke; Kozuki, Amane; Sasaki, Shinya; Soga, Yoshimitsu; Ando, Kenji
Purpose: To examine with intravascular ultrasound (IVUS) the crossing pathways of the TruePath reentry device during primary antegrade recanalization of infrainguinal chronic total occlusions (CTOs).Methods: Between July 2017 and September 2018, a prospective multicenter study enrolled 143 consecutive patients (mean age 75±9 years; 101 men) with 146 CTOs treated in an antegrade approach using the TruePath reentry device with IVUS assessment of the crossing pathway in successful cases. Outcome measures were complete success (reentry device reached the distal true lumen), assisted success (reentry device use followed by a conventional guidewire to reach the distal true lumen), reentry device crossing route by IVUS assessment, and procedure- and device-related complications. Regression analyses were employed to identify any relevant associations between baseline patient variables and the outcome measures; results are presented as the odds ratio (ORs) and 95% confidence interval (CI).Results: Complete success was achieved in 82 (56.2%) lesions; any success (complete plus assisted) was documented in 117 (80.1%) lesions. Four (3%) perioperative device-related complications were observed. The crossing route was intraplaque for most of the total crossing distance in both complete success cases (95.3%±13.2%) and any success cases (94.8%±14.4%), with relatively short subintimal (3.6%±10.2% and 4.2%±11.2%, respectively) or intramedial (1.2%±5.8% and 1.0%±5.4%, respectively) crossing. CTO length was a significant risk factor for not achieving complete success (OR 1.74, 95% CI 1.13 to 2.68, p=0.012), and a history of failed revascularization was associated with not achieving any success (OR 6.40, 95% CI 1.28 to 28.9, p=0.038).Conclusion: The intraplaque route was the primary pathway taken by the TruePath reentry device as it crossed infrainguinal CTOs. Crossing rates were acceptable, with few device-related complications. However, a longer CTO length and a failed revascularization history negatively affected the success rate.